2019
DOI: 10.1111/bph.14762
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial TRPV4 channels modulate vascular tone by Ca2+‐induced Ca2+ release at inositol 1,4,5‐trisphosphate receptors

Abstract: Background and Purpose The TRPV4 ion channels are Ca 2+ permeable, non‐selective cation channels that mediate large, but highly localized, Ca 2+ signals in the endothelium. The mechanisms that permit highly localized Ca 2+ changes to evoke cell‐wide activity are incompletely understood. Here, we tested the hypothesis that TRPV4‐mediated Ca 2+ influx activates Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 97 publications
(187 reference statements)
2
63
0
Order By: Relevance
“…Multiple ion channels increase Ca 2+ levels in native ECs, including ion channels of the transient receptor potential (TRP) family (Earley et al 2009;Sonkusare et al 2012;Pires et al 2015;Sullivan et al 2015;Hong et al 2018) and inositol triphosphate receptors (Ledoux et al 2008b;McCarron et al 2010;Bagher et al 2012;Tran et al 2012;Heathcote et al 2019). The TRP vanilloid 4 (TRPV4) channel has emerged as an important Ca 2+ -influx pathway in ECs from systemic and pulmonary resistance arteries (Bagher et al 2012;Sonkusare et al 2014;Marziano et al 2017;Hong et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple ion channels increase Ca 2+ levels in native ECs, including ion channels of the transient receptor potential (TRP) family (Earley et al 2009;Sonkusare et al 2012;Pires et al 2015;Sullivan et al 2015;Hong et al 2018) and inositol triphosphate receptors (Ledoux et al 2008b;McCarron et al 2010;Bagher et al 2012;Tran et al 2012;Heathcote et al 2019). The TRP vanilloid 4 (TRPV4) channel has emerged as an important Ca 2+ -influx pathway in ECs from systemic and pulmonary resistance arteries (Bagher et al 2012;Sonkusare et al 2014;Marziano et al 2017;Hong et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the efficacy of XeC as a selective inhibitor of IP 3 Rs has been questioned (Saleem et al 2014) and off target effects other than IP 3 R inhibition have been reported for this agent (Sergeant et al 2001). Experiments performed on isolated isoforms of the IP 3 R (IP 3 R1-3) in expressed systems and on IP 3 R-dependent Ca 2+ signalling in vascular endothelial cells have demonstrated that caffeine is an effective antagonist of IP 3 R1 (dominant isoform in ICC) (Baker et al 2016;Drumm et al 2017Drumm et al , 2019b at concentrations of 10 mM (Saleem et al 2014;Heathcote et al 2019). Although caffeine is also known to be a modulator of RyRs, the lack of effect of the RyR antagonist on ICC-SS Ca 2+ signals ( Fig.…”
Section: Sources Of Ca 2+ Required For Icc-ss Activitymentioning
confidence: 99%
“…We next examined the relationship between spontaneous Ca 2+ activity and IEL holes ( Figure S10 and Table S8). In contrast to ACh-evoked Ca 2+ activity, basal (unstimulated) Ca 2+ events are mostly subcellular waves and the initiation site of individual events can be readily identified (see also 29,32 ). Importantly, irrespective of diet, we found that endothelial Ca 2+ events occurred closer to MEPs than would be expected than if they occurred randomly throughout the cytoplasm ( Figure S10C-D and Table S8).…”
Section: Local Ca 2+ Signalingmentioning
confidence: 99%